2013
DOI: 10.1080/15222055.2013.837126
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Comparisons among Natural‐Origin, Hatchery‐Origin, and Captive‐Reared Female Spring Chinook Salmon from the Tucannon River, Washington

Abstract: We examined the effects of hatchery rearing on FL, weight, egg size, fecundity, relative fecundity, and reproductive mass of female spring Chinook Salmon Oncorhynchus tshawytscha from a population that had been in captivity for 0 (natural‐origin), 18 (hatchery‐origin), and 48 (captive‐reared broodstock) months. Age‐4 captive‐reared broodstock females that were reared for their entire life in the hatchery environment had significantly lower mean FL, weight, fecundity, relative fecundity, and reproductive mass, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The Schroder et al (2008) study accounted for differences in breeding success due to female size and fecundity, but it is not possible to do so in wild environments when the physical characteristics of each individual spawner cannot be measured pre-and postspawning. This could explain results such as those reported in Thériault et al (2011) and Gallinat and Chang (2013), where the observed differences in reproductive success for first-generation hatchery-origin spawners did not appear to be passed on to progeny. Still, the results from a number of other recent studies showing reduced reproductive success for hatchery-origin spawners (e.g., Araki et al 2007b;Williamson et al 2010;Christie et al 2011Christie et al , 2012Hayes et al 2013) suggest that all hatchery programs should proceed with caution and implement careful monitoring programs when hatchery-origin fish are known to escape onto the natural spawning grounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Schroder et al (2008) study accounted for differences in breeding success due to female size and fecundity, but it is not possible to do so in wild environments when the physical characteristics of each individual spawner cannot be measured pre-and postspawning. This could explain results such as those reported in Thériault et al (2011) and Gallinat and Chang (2013), where the observed differences in reproductive success for first-generation hatchery-origin spawners did not appear to be passed on to progeny. Still, the results from a number of other recent studies showing reduced reproductive success for hatchery-origin spawners (e.g., Araki et al 2007b;Williamson et al 2010;Christie et al 2011Christie et al , 2012Hayes et al 2013) suggest that all hatchery programs should proceed with caution and implement careful monitoring programs when hatchery-origin fish are known to escape onto the natural spawning grounds.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported fitness differences, though these are attributed in part to nonheritable environmental effects (Knudsen et al 2006;Beacham 2010;Chittenden et al 2010;Gow et al 2011;Thériault et al 2011;Ford et al 2012;Gallinat and Chang 2013). Still other studies have reported few or no negative effects on fitness due to hatchery influence (Heggenes et al 2006;Sharma et al 2006;Araki et al 2007a;Schroder et al 2008Schroder et al , 2010Berejikian et al 2009;Hess et al 2012;Anderson et al 2013).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Success of captive broodstock programs has largely been measured by the number of eggs, fry, and adults produced in captivity, rather than the performance of the fish after release (ISRP 2004). Studies also conducted on populations that have a common genetic background provide a chance to understand the mechanisms behind changes caused by the hatchery environment (Gallinat and Chang 2013). Fecundity, egg size, spawning timing, and length at age of the captive broodstock for this population have been published elsewhere (Gallinat et al 2009;Gallinat and Chang 2013).…”
mentioning
confidence: 99%
“…Studies also conducted on populations that have a common genetic background provide a chance to understand the mechanisms behind changes caused by the hatchery environment (Gallinat and Chang 2013). Fecundity, egg size, spawning timing, and length at age of the captive broodstock for this population have been published elsewhere (Gallinat et al 2009;Gallinat and Chang 2013). Progeny from the captive broodstock program reared in parallel with the supplementation program at the Lyons Ferry Hatchery complex offered the opportunity to compare the in-hatchery and postrelease performance of these two strategies.…”
mentioning
confidence: 99%